Effectiveness of Pharmacological Agents and Validation of Diagnostic Scales for the Management of Paroxysmal Sympathetic Hyperactivity in Hispanics - Abdelhakiem, Alaa K.; Torres-Reveron, Annelyn; Padilla, Juan M. (Frontiers in Neurology, 2020)
The identification and treatment of paroxysmal sympathetic hyperactivity (PSH) still present a significant challenge. We assessed the efficacy of pharmacological agents in treating PSH symptoms and the validity of the diagnostic scales in a cohort of Hispanic patients. A retrospective chart review of cases from a single hospital was conducted in 464 records. Exclusion criteria included underlying conditions such as severe infection. Only nine patients remained in the cohort after examining their clinical records, corresponding to the following diagnoses: traumatic brain injury, subdural hemorrhage, anoxic or ischemic encephalopathy, pneumocephalus, and cerebral palsy. Using the PSH likelihood scale, six of the nine patients were identified with a score of 17 or higher, corresponding to a “probable” PSH, and three patients obtained a score between 8 and 16, corresponding to a “possible” PSH diagnosis. The top three classes of medications used were beta-blockers, antipyretics, and opioids. Benzodiazepines and neuromodulators were also frequently used in patients with trauma, but not in the ones with non-traumatic injuries. Interestingly, 75% of the patients have prescribed levothyroxine as a home medication after the PSH presentation. Medication administration did not follow a specific pattern, suggesting high variability in the management of PSH within our setting, requiring further research. Our results suggest that the pituitary axis might be involved in the progression of PSH. Establishing a specific medical code (e.g., ICD-10) describing PSH as a single entity is essential for appropriate identification and management.